Identifying indicators of community participation‐promoting efforts within coordinated specialty care: A modified e‐Delphi study of stakeholder perspectives - Thomas, Elizabeth C.; Jones, Nev; Shern, David L.; Salzer, Mark S. (Early intervention in psychiatry, 2022)
Aim: Community participation in occupational, social, recreational, and other domains is critically important during young adulthood. Coordinated Specialty Care (CSC) programs provide developmentally tailored care to young adults experiencing early psychosis within the United States, but little is known about the breadth of efforts to promote community participation. This study aimed to develop and evaluate indicators of these efforts based on the perspectives of a national multi‐stakeholder group. Methods: Seventeen stakeholders (i.e., young adults with early psychosis, family members, experts by profession) participated in a modified e‐Delphi study, conducted in two rounds. The purpose of round one was to generate a comprehensive list of community participation‐promoting indicators. During round two, stakeholders rated the importance and feasibility of the implementation of each indicator. Descriptive statistics and percentage of agreement regarding round two ratings were assessed. Results: During round one, 186 indicators of activities and/or practices designed to promote community participation were identified; this list was reduced to 44 by eliminating redundancies or indicators not related to community participation. In round two, we found broad agreement regarding the importance, but significant variation in perceived feasibility of indicators. The highest‐rated indicators in both categories pertained to staff knowledge (regarding barriers and supports to participation and the importance of participation to health) and strategies for addressing participation barriers. Conclusions: This study is expected to facilitate the identification and development of promising CSC activities and practices designed to promote community participation among young adults while potentially also enhancing engagement in services and improving clinical outcomes.